PENGARUH SERTIFIKASI, MOTIVASI, KOMPETENSI TERHADAP KINERJA GURU SEKOLAH DASAR NEGERI (SDN) DI KECAMATAN PAKISAJI KABUPATEN MALANG - Yuda Putra Wahyudi; Hadi Sunaryo (E-JRM : Elektronik Jurnal Riset Manajemen, 2017)
ABSTRACT The results of this study indicate that certification significantly influence the performance, motivation significant effect on performance, competence significantly influence the performance, and simultaneously there are significant positive and significant variables certification, motivation, and competence on the performance of Teachers Elementary School (SDN) in the District Pakisaji Malang. In this study can be interpreted that the higher the value of certification, motivation and competence the higher the value of the performance either individually among the independent variables on the dependent variable and simultaneously in the independent variable on the dependent variable Keywords: certification, motivation, competence, and performance